Study of Maternal and Fetal Outcome among Booked and Unbooked Patients at tertiary Hospital - Subedi, Shanti Sunuwar; Bhansakarya, Rakina; Sharma, Sajjan Kumar (Birat Journal of Health Sciences, 2020)
Introduction: To evaluate the maternal and perinatal outcome in booked and unbooked cases.Objectives: To assess the maternal and fetal outcomes in unbooked and booked patients.Methodology: This was a cross-sectional comparative study conducted in the Department of Obstetrics and Gynecology from Augustti2019 to January 2020. Using a convenient sampling technique, 204 samples were taken and cross-sectional study was done.Results: There were total 204 cases in this study;102were booked and 102 were unbooked. In this study, 85(83%) of booked cases were educated up to secondary level as compared toti65 (64%) of unbooked cases. There was no significant difference in Apgar score in 1 and 5 minute between booked and unbooked cases. More babies in the unbooked group were transferred to NICU as compared to the booked group and the difference was significant (9.8%vs 1.9%). Greater proportion of booked cases had spontaneous vaginal delivery (81.3% vs 59.8%) and complications like preterm delivery, anemia, preeclampsia/ eclampsia, complicated labor and puerperal sepsis was also less in the booked group.Conclusions: The study showed that unbooked mothers and their newborns had higher chance of having complications.